Social media as a strategic marketing tool in the Sicilian wine industry: Evidence from Facebook - Antonino Galati; Maria Crescimanno; Salvatore Tinervia; Francesco Fagnani (Wine Economics and Policy, 2017)
Over the last few years, many companies have integrated social media, and social networking sites in particular, into their communication and media plan, leading to a deep transformation of the organizational models and changing the companies' marketing dynamics. This study has dual aims: first, to recognize and validate the firm's social media (SM) efforts in its use of the Facebook platform; second, to examine the relationships among the firm's SM efforts and some firm and managerial characteristics. In order to achieve these research aims, data on 45 wineries were collected and analysed, using a model that considers three different dimensions of the firms' activity on the social platform. The results show that mainly small firms, in physical and economic terms, led by managers with a higher educational level, have become more involved in SM as shown by high values of intensity, richness, and responsiveness. On the contrary, large companies' social-media efforts have been more modest. The results of this study need to be interpreted within the context for which our research was designed. Findings have some theoretical and practical implications.
Keywords: 330; Facebook; Firms' social media efforts; Italy; Wine industry